A model of brand engagement in online brand communities: Co-creating value for the brand and the community - Alotaibi, Meshaal Hamad (Curtin University, 2016)
Utilising qualitative and quantitative methods, this thesis examines customer engagement in value co-creation from a customer perspective. This thesis provides a model of brand engagement behaviours in online brand communities by taking into account co-creating value for the brand and the community. The findings identify three types of engagement behaviours - helping oneself, helping others and helping the firm - and provide an empirical model explaining antecedents and outcomes of each engagement behaviour.